Obreros al servicio de la revolución: la representación de los intelectuales ecuatorianos en los años 30 [Dossier Literatura Ecuatoriana (Siglos XX-XXI): otros desciframientos (Ponencias presentadas en el Congreso de la Asociación de Ecuatorianistas, Quito, 20-21 de julio de 2015)] - Haddaty Mora, Yanna (2016)
The representation of the artist or man of letters “as an intellectual worker”, heir to the socialist press of the late nineteenth century, is a topic in the Latin American and European leftist cultural publications of the first third of the twentieth century, although it never works in an identical manner. This essay attends to its particular articulation in the Ecuadorian case during the decade of the 30. To do so, it initially starts in the search for non-literary texts, the leftist press, some private correspondence; and then goes on to revise later the pages of poetry and narrative that include in the same way this mediation of the intellectual.